The experimental study of CFRP interlayer of dissimilar joint AA7075-T651/Ti-6Al-4V alloys by friction stir spot welding on mechanical and microstructural properties - Nasir, Tauqir; Kalaf, Omer; Asmael, Mohammed; Zeeshan, Qasim; Safaei, Babak; Hussain, Ghulam; Motallebzadeh, Amir (De Gruyter Poland Sp Z O O, 2021)
The present study focused on two dissimilar metal alloys: AA7075-T651 and Ti-6Al-4V alloys with additional carbon fiber-reinforced polymer (CFRP) as an interlayer were welded together by friction stir spot welding (FSSW). The effect of welding parameters (rotational speed and dwell time) and carbon fiber-reinforced polymer on mechanical and microstructural properties of a weld joint was investigated. The obtained results explore the parametric effects on mechanical properties of the weld joint. The maximum tensile shear load 2597.8 N was achieved at the rotational speed of 2,000 rpm and dwell time of 10 s. While at the same rotational speed, 54.7% reduction in the tensile shear load was attained at shorter dwell time of 5 s. Therefore, dwell time plays an important role in the tensile shear load of a weld joint. The scanning electron microscope (SEM-EDS) results show the formation of intermetallic compound of Ti3Al and Ti-Al-C that significantly affect the mechanical and microstructural properties of the weld joint. Moreover, the effect of the rotational speed on micro-hardness was found at significant than dwell time. The micro-hardness of the weld joint increase by 18.90% in the keyhole rather than the stir zone and the thermomechanical affected zone, which might be due to the presence of ternary (Ti-Al-C) intermetallic compound.
Keywords: friction stir spot welding; titanium alloys; aluminum alloys; interlayer; carbon fiber-reinforced polymer; welding parameters